Determinants of Load Capacity Factor in Nigeria: Implications for Sustainable Development - Dada James Temitope; Tabash Mosab I.; Al-Faryan Mamdouh Abdulaziz Saleh; Akinbobola Temidayo Oladiran (Economics and Culture, 2025)
Motivated by the growing level of ecological degradation and the need to accomplish sustainable development, this study examines the influence of energy consumption, institutions, urbanization, education, and economic growth on the load capacity factor (LCF) of Nigeria.